Mechanical And Thermal Issues In Downsize Engine: A Review - Ahmed, Aqeel; S. Wahab, M.; A. Raus, A.; Kamarudin, K.; S. Bala1; Mohd Badli Ramli, A. (International Journal of Engineering and Technology, 2018)
This work is highlighting the previous research work on the mechanical and thermal issues in the Downsize Engine. By using downsize engine technology, the consumption of fuel and emission decreased by reducing geometrical dimensions of combustion chamber parts and thermal and mechanical efficiencies increased by increasing the power output bywith the help pg using turbochargers. Using turbochargers, a super knock could result from the pre-ignition and induces severe oscillation and leads to the thermal and mechanical stresses on account of diminished mass and geometrical aspects of the various parts employed in the combustion chamber (CC). The increment in thermal and mechanical stresses may damage the main part(s) (piston) of the combustion chamber. In focusing the above facts; the shape design and the best material is the right choice for the better combustion and long life of the CC parts (piston) in downsizing engine respectively.Â Â